Correct Answer - Option 3 : 70

Given,

Average age of A, B and C, 3 years ago = 45

Average age of A, B and C at present = 45 + 3 =48

Sum of ages of A, B and C (A + B + C) = 48 × 3 = 144

Given,

Average age of B and C, 4 years ago = 35

Average age of B and C at present = 35 + 4 = 39

Sum of ages of B and C (B + C) = 39 × 2 = 78

Age of A at present= (A + B + C) - (B + C)

= 144 - 78

= 66

Age of A after 4 years = 66 + 4 = 70 years.

So, the age of A, after 4 years is **70 years**.

Hence, the correct answer is **70**.